ANALISIS STRATEGI PEMASARAN TABUNGAN EASY WADIAH PADA BSI KCP PULAU PUNJUNG - Aga Riani, Sindi; Ismail (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
Easy Wadiah Savings is a savings product in the form of a deposit with a bank that can be deposited during working hours and withdrawn at any time. Besides that, many people around BSI KCP Pulau Punjung 1 do not use the Easy Wadiah Savings product, one of which is Sungai Belit Village on the grounds that there is no difference between the savings at BSI and conventional banks. The problem in this research is that BSI has not utilized social media to promote its products widely. The purpose of this study was to determine the marketing strategy, and the constraints on the marketing of Easy Wadiah Savings at BSI KCP Pulau Punjung 1, Dharmasraya. This research is a field research with a qualitative approach. Data was collected by means of observation, interviews, and documentation studies. Based on the research that has been done, the marketing strategy and constraints on BSI KCP Pulau Punjung 1 are in the promotion strategy consisting of several elements, namely: advertising, personal selling, sales promotion, public relations. Where these elements have not been implemented perfectly, there are still some shortcomings, such as promotions in advertising which are less active on social media and public relations that are not yet widespread.